2019
DOI: 10.1002/anie.201905501
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oxygen Evolution Activity of Nickel Oxyhydroxide by Electrolyte Alkali Cations

Abstract: Herein, the effect of the alkali cation (Li + ,Na + ,K + , and Cs + )inalkaline electrolytes with and without Fe impurities is investigated for enhancing the activity of nickel oxyhydroxide (NiOOH) for the oxygen evolution reaction (OER). Cyclic voltammograms showthat Fe impurities have asignificant catalytic effect on OER activity;h owever,b oth under purified and unpurified conditions,the trend in OER activity is Cs + > Na + > K + > Li + ,suggesting an intrinsic cation effect of the OER activity on Fe-free N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
228
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(253 citation statements)
references
References 54 publications
21
228
1
3
Order By: Relevance
“…Other factors previously proposed to explain the cation effect of OER, including enhanced water diffusion in the interlayer space and cation‐induced exfoliation can be ruled out because our LDH samples are ultrathin and have abundant accessible surface sites, and because our samples are not exfoliated in CsOH. We can also exclude a stabilizing interaction of NiOO − with Cs + because we did not observe an evolution of a shoulder peak between 930–950 cm −1 in CsOH (Supporting Information, Figures S12 and S13) . To probe the possibility of electric field effect due to Cs + adsorption, we measured OER in tetramethylammonium hydroxide (TMAOH) solution.…”
Section: Figurementioning
confidence: 99%
“…Other factors previously proposed to explain the cation effect of OER, including enhanced water diffusion in the interlayer space and cation‐induced exfoliation can be ruled out because our LDH samples are ultrathin and have abundant accessible surface sites, and because our samples are not exfoliated in CsOH. We can also exclude a stabilizing interaction of NiOO − with Cs + because we did not observe an evolution of a shoulder peak between 930–950 cm −1 in CsOH (Supporting Information, Figures S12 and S13) . To probe the possibility of electric field effect due to Cs + adsorption, we measured OER in tetramethylammonium hydroxide (TMAOH) solution.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, as previously discussed, the presence of cations can also affect the OER activity by self-insertion into the porous structure of NiOOH in addition to hydration enthalpy which modifies the energetics of the intermediates and the water structuring effect. 90 Future work is thus needed to fully understand and dissociate all these different effects. In light of the effect of ions observed on the performances of the most active OER catalysts, one must therefore consider more than just the binding energy of oxygen intermediates on the surface of the catalyst.…”
Section: Controlling the Water Structure In The Environment Of Activementioning
confidence: 99%
“…Notably, slightly before the contribution of Shinagawa, Obata, and Takanabe, Schuhmann and co‐workers demonstrated that by increasing the ionic strength of the electrolyte the selectivity ratio of the competing chlorine and oxygen evolution reactions significantly shifts towards the side of chlorine evolution, while Koper and co‐workers reported that the presence of alkali cations enhances the activity of Ni‐oxyhydroxides in the oxygen evolution reaction . Similarly, Bandarenka and co‐workers discussed the influence of alkali cations on the HER activity, demonstrating that activity trends correlate with the hydration energy of the corresponding alkali cations present in the electrolyte …”
Section: Acknowledgementsmentioning
confidence: 99%